Urgensi evaluasi ketakwaan diri pada lembaga pendidikan Islam dalam bentuk aplikasi - Afiffudin; Hafidhuddin, Didin (TAWAZUN: Jurnal Pendidikan Islam, 2025)
The level of piety of students is the main indicator of the success of national education as stated in Law No. 20 of 2003. Schools labeled as Islamic have a greater responsibility in producing a faithful and pious generation. However, the evaluation of Islamic Religious Education in schools generally only measures the cognitive aspect and has not touched the piety aspect as a whole. This research aims to develop a piety measurement tool based on three main criteria: faith, Islamicity, and piety. The three criteria were formulated through FGDs with local scholars and developed into 25 question items, which represent the six pillars of faith, five pillars of Islam, and 14 indicators of ihsan behavior. Content validation was conducted by 15 Islamic boarding school teachers with average CVI values: relevance 0.90; simplicity 0.89; and clarity 0.93. The application trial was conducted on 67 congregants of Majelis Taklim in South Jakarta, with the results: 12% Muttaqin Good, 45% Excellent, and 43% Great. The application is easy to use and produces an online evaluation certificate, along with suggestions for improving worship. This model has the potential to be used in schools or certain community groups as a practical and standardized piety measurement tool. Abstrak Tingkat ketakwaan peserta didik merupakan indikator utama keberhasilan pendidikan nasional sebagaimana tercantum dalam UU No. 20 Tahun 2003. Sekolah berlabel Islam memiliki tanggung jawab lebih besar dalam mencetak generasi yang beriman dan bertakwa. Namun, evaluasi Pendidikan Agama Islam di sekolah umumnya hanya mengukur aspek kognitif dan belum menyentuh aspek ketakwaan secara menyeluruh. Penelitian ini bertujuan mengembangkan alat ukur ketakwaan berbasis tiga kriteria utama: keimanan, keislaman, dan keihsanan. Ketiga kriteria tersebut dirumuskan melalui FGD dengan ulama setempat dan dikembangkan menjadi 25 butir pertanyaan, yang mewakili enam rukun iman, lima rukun Islam, dan 14 indikator perilaku ihsan. Validasi isi dilakukan oleh 15 guru pondok pesantren dengan nilai CVI rerata: relevance 0,90; simplicity 0,89; dan clarity 0,93. Uji coba aplikasi dilakukan pada 67 jamaah Majelis Taklim di Jakarta Selatan, dengan hasil: 12% Muttaqin Good, 45% Excellent, dan 43% Great. Aplikasi ini mudah digunakan dan menghasilkan sertifikat evaluasi secara daring, disertai saran peningkatan ibadah. Model ini berpotensi digunakan di sekolah atau kelompok masyarakat tertentu sebagai alat ukur ketakwaan yang praktis dan terstandar.